Impacto do biofilme de Escherichia coli enteroagregativa na susceptibilidade a antimicrobianos - Gonçalves, Mariana Teixeira (2017)
Enteroaggregative Escherichia coli (EAEC) is an emerging pathogen that causes acute and persistent diarrhea worldwide. Biofilm formation, a notable aspect of its pathogenicity, is related to the persistence of infection and requires antimicrobial treatment, and the use of ampicillin, quinolone, sulfamethoxazole/trimethoprim and tetracycline is suggested. As usual techniques of determination of susceptibility do not reflect biofilm activity we aimed to determine the minimum inhibitory concentration of biofilm (MBIC) of nine antimicrobials of eight classes, and to determine the minimum concentration of biofilm eradication (MBEC) by means of (peg-lid), for EAEC clinical samples, for prototype strains EAEC042 and EAEC17-2 and for reference strain ATCC 25922. Minimum inhibitory concentration (MIC) was determined for 35 samples per agar dilution and 20 antimicrobial susceptible samples were selected for ampicillin, cefotaxime, ceftriaxone, chloramphenicol, ciprofloxacin, tetracycline and tobramycin and 19 to sulfamethoxazole/trimethoprim for determination of MBIC. Biofilm was formed in Dulbecco's Modified Eagle Minimum Medium with 0.4% glucose and the biofilm maturation time and formation intensity were determined both in the microplate well and in the peg-lid. The biofilm maturation was achieved with 24 h; eight and 12 samples were classified as strong and weak biofilm forming, respectively. 24 h Biofilm was subjected to folded dilutions of the antimicrobials in Mueller-Hinton broth adjusted with cation and optical density at 650 nm (OD650) was measured after ultrasonic biofilm recovery, before and after incubation at 37 ° C for 6 hours. MBIC revealed that the biofilms were: (i) 100% (20/20) resistant to tetracycline, chloramphenicol and sulfamethoxazole/trimethoprim and 90% (18/20) to ampicillin; (ii) 90% (18/20) with intermediate resistance to ceftriaxone and cefotaxime, (iii) 95% (19/20), ciprofloxacin-sensitive, 80% (16/20) to cefoxitin and 75% (15/20) to tobramycin. Biofilm increased the inhibitory concentration of the antimicrobials by 2 to 4,266.7 times the MIC and the strong forming samples increased the MBIC of ampicillin, ceftriaxone and tobramycin more than the weak formers (p <0.05). The MBEC was always superior to the MBIC and to the last concentration tested, with the exception of cefoxitin and cefotaxime for a sample. Biofilm maturation time of 48h, and 72h did not interfere with MBIC. In conclusion, ciprofloxacin presented excellent activity for EAEC biofilm, followed by cefoxitin and tobramycin, and antimicrobials that were ineffective as ampicillin, sulfamethoxazole/trimethoprim and tetracyclines for the treatment of EAEC infection should not be recommended.